SUPPLY CHAIN RESILIENCE: CALCULATION OF MAXIMUM TOLERABLE DOWNTIME (MTD) AND OPTIMUM STOCK LEVEL WITH A RISK-BASED APPROACH - Yoga Wishnu Pradana; Nur Budi Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The coal mining sector faces major challenges in maintaining operational continuity due to market fluctuations, logistics disruptions, and external uncertainties. This study evaluates the supply chain resilience of PT XYZ using a risk-based approach. The main objectives are to calculate the Maximum Tolerable Downtime (MTD) and determine the optimum inventory level adjusted to the company's financial risk tolerance limit. Currently, PT XYZ is experiencing an imbalance between production and sales, causing coal stock to approach the maximum capacity limit of 14.7 million tons. The increase in average stock from 2020–2024 has an impact on high storage costs and operational risks. This study integrates operational data, risk assessment models, and quantitative methods to convert financial risk limits into operational limits in tonnage units. The result is a predictive model that functions as an early warning system to help companies maintain operations within safe limits and improve decision making amid uncertainty.